Analisis Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Pengukuran Kinerja UMKM di Wilayah Depok - Titis Wahyuni; Marsdenia Marsdenia; Istiadi Soenarto (Program Pendidikan Vokasi Universitas Indonesia, 2016)
AbstractThe purpose of this study is to examine the effect of application accounting information system on SMEs performance measurement in Depok region. The number of samples taken were 30 SMEs using purposive sampling method with the critreria listed in the official city of Depok. The data was collected using questionnaires distributed to respondents and the analysis technique used in this research is logistic regression to determine whether there is any effect on the application of accounting information systems for the decrease or increase the performance of SMEs. The results of this study based on the analyses conducted found that the value of Negelkerke’s R Square for ROA is 1,574, which indicates that the dependent variable that can be explained by the independent variable is at 1.4%, while the rest, 98,6% is explained by other variables not included in this study. The value of Negelkerke's R Square for ROE is 0.002 which indicates that the dependent variable that can be explained by the independent variable is 0.2%, while the rest, ie 99.8% explained by other variables not included in this study.Keyword; accounting information system, SMEs, ROA, ROE